Kemampuan Siswa SMP dalam Menyelesaikan Persoalan Matematika Dasar - Sa'di, Dianti Ramadhani; Firdaus, Naswa Putri Nur; Sinaga, Ruth Daniella Hasian; Yonvitra, Nashaliya Hasifa (Jurnal Pendidikan Matematika, 2024)
Basic mathematical abilities are having the basic ability (being able) to think deductively in building theories and communicating the results of scientific activities correctly and being able to communicate accurate, precise, artificial language in mathematics. Basic mathematical abilities also include the basic skills needed to understand and solve mathematical problems at a basic level. This research was conducted with the aim of describing the profile of students' basic mathematical abilities in solving basic problems. Elementary schools have a key role in building the foundations of mathematics education for students. Basic mathematics is taught at this level to help students understand basic mathematical concepts necessary in everyday life and to prepare them for further mathematics learning at higher levels. It is important to ensure that the mathematics foundation built at the primary school level is strong, as this will influence students' understanding and success at higher levels of education. Junior high school is the second level of school after elementary school, and at this stage students are taught about basic mathematics or easy mathematics that usually occurs in everyday life. Such as calculations which develop students' basic calculation skills, understanding number concepts such as fractions, decimal numbers and whole numbers, addition, multiplication and division. Using mathematics in real contexts, so that students can see the relevance and usefulness of mathematics in everyday life.